Labels on seafood products in different European countries and their compliance to EU legislation. (December 2021) - Paolacci, Simona; Mendes, Rogério; Klapper, Regina; Velasco, Amaya; Ramilo-Fernandez, Graciela; Muñoz-Colmenero, Marta; Potts, Tavis; Martins, Sandra; Avignon, Solene; Maguire, Julie; De Paz, Enrique; Johnson, Martin; et al.
Abstract: The increasing consumption of seafood products raises concerns over their sustainability and the conservation of marine resources. Seafood traceability, enabled by a regulated labelling system, is important to prevent overexploitation of these resources. The regulations (EU) No.1169/2011 and (EU) No 1379/2013 are the European legislative tools that specify the mandatory information that must be present on seafood labels. The present study analysed the labels of seafood products sold in different European countries in order to verify the presence of mandatory information required by EU regulations currently in place. The results show that there is a difference in compliance among groups of products and among countries. The country with the lowest level of compliance was The United Kingdom (still part of EU when the study was carried out), with an overall compliance of 63.7%. The country with the highest level of compliance was Portugal (87.2%). Across all the countries analysed, supermarkets were more compliant than fishmonger's shops and Processed Prepacked products were more conformed best to the EU labelling legislation when compared to Unprocessed Non-Prepacked products. Differences among different areas of the same country were also observed. Fishing gear, scientific name, fishing/production method and date of freezing were the types of information most frequently missing on the labels examined. The results of this study pose the bases for further actions, that can be taken by relevant institutions, to improve compliance throughout the supply chain.